Literature Review: Effects of Palm Oil Fuel Ash Adsorbent Mass Variation on Adsorption Process Efficiency in Water Treatment - Vania Talitha Ananta; Siska Noviana; Hadistya Suryadri; Rara Ayu Lestary; Rosmawati Sipayung (Research in Chemical Engineering, 2026)
Palm Oil Fuel Ash (POFA) has excellent potential as an adsorbent for heavy metals, especially zinc (Zn), because it is able to provide a high absorption percentage. The purpose of this literature study is to systematically examine the effect of variations in the mass of Palm Oil Fuel Ash (POFA) adsorbent on the efficiency of the heavy metal adsorption process in water treatment, as well as to identify the most effective activator for POFA-based adsorbents based on the results of previous studies. The literature study method was carried out by reviewing and comparing relevant national and international scientific articles through Google Scholar, Garuda, and SINTA-accredited journal databases, with a focus on the relationship between POFA adsorbent mass and adsorption efficiency. Commonly used activators include NH₄Cl, HCl, NaOH, and KOH, with the best results varying for each type of POFA modification. Unmodified POFA showed optimum performance when activated using NH₄Cl, with an adsorption percentage reaching 98.65% at a mass of 10 grams, while zeolite POFA gave the highest results with HCl activator, namely 98.77% with a mass of only 2 grams. In contrast, silica POFA showed a lower adsorption capacity, with an adsorption percentage of 44.50% at a mass of 25 grams. Overall, these results indicate that POFA zeolite is the most effective adsorbent in the adsorption of zinc metal compared to unmodified POFA and silica POFA because it is able to achieve high efficiency with the use of less adsorbent mass.